Towards the characteristics of unified interface in short message service (SMS) for value added services (VAS) application: a case study in Celcom / Nurulhuda Mustofa - Mustofa, Nurulhuda (2007)
Mobile messaging is an important and quickly growing business for the mobile network operators and is becoming increasingly important to third-party content providers as well. Providing content services on the mobile networks offers a good source of revenue as the user base and the means to bill for the services is already in place. The problem is that there is not one specific standard for interconnection between value added service applications and the mobile network. The mobile network standards only cover the connectivity within the network, leaving the external connections out of scope. The lack of management features provided by the interconnectivity solutions is also a problem. The mobile terminals on the GSM network currently support a variety of different message formats and the range of different protocols used to connect service applications is even larger. This report describes the technology and business models for providing messaging services, concentrating on the interconnectivity problems from both the mobile network operator and the service providers' point of view. As a solution to the problems identified, both protocol standardization work and a category of messaging middleware such as Message Gateways and Routers, is introduced.